Indoor localization system using particle swarm optimization - Alhammadi, Abdulraqeb Shaif Ahmed; Hashim, Fazirulhisyam; Shami, Tareq M. (2015)
Tracking the user location in indoor environment becomes substantial issue in recent research. Location based services have been used in many mobile applications as well as wireless sensor networks. One of the techniques that are used in localization systems is particle swarm optimization (PSO). This technique is a stochastic optimization based on the movement and velocity of particles. In this paper, we introduce an algorithm using PSO for indoor localization system. The suggested algorithm is called circular PSO (CPSO) which depends on the distribution of the particles at each access point. The simulation results show the effectiveness of the suggest algorithm on average location error.